ETIKA APARATUR PELAYANAN PUBLIK “Tinjauan Atas UU Aparatur Sipil Negara” - Irawanto . (REFORMASI, 2015)
Society as the highest sovereign philosophically very worthy of getting the best services of the State Civil Apparatus (ASN). Law Decree No. 5/2014 on the State Civil Apparatus arranged ASN's role is to realize the national development through a professional public service, free from political interference, and free from corruption, collusion, and nepotism. But reality shows ASN service in Indonesia still indicates a violation of moral and ethical, the bias of particular interest, as well as public service management processes are fully engineered and camouflage. In the practice of governance in Indonesia ethical problems is a necessity. Ethical problems of the services provided by the ASN for this is still limited to a commitment that is taken for granted, and not yet a reality in everyday behavior. Whereas in the legislation contains a code of conduct based on the ethics of religious, cultural, social and ethical governance.